(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
A new radiolitid rudist, Paronella ? ostunensis n. sp. from the Late Cretaceous of Apulia is described. The excellent preservation of the fossil material made possible to discuss the validity of the genus Paronella Wiontzek, 1934.